Beta Blockers as Salvage Treatment in Refractory Septic Shock Complicated With Dynamic Left Ventricular Outflow Tract Obstruction: A Rare Case Presentation - Catalá-Ruiz Pablo MD; Andaluz-Ojeda David MD PhD; Veras Carlos MD; Aparisi Álvaro MD; Hinojosa Williams MD; Iglesias Carolina MD; Marcos Marta MD; Nogales-Martin Leonor MD; Amat Ignacio MD PhD; Alberto San Román MD PhD (SAGE Publishing, 2021)
Hypotension is the main finding in patients admitted to an intensive care unit (ICU) with the diagnosis of septic shock and it is related to worse outcomes. In these patients, several underlying causes of hypotension may co-exist, including vasoplegia, hypovolemia, drug-mediated venodilation, or myocardial dysfunction. Nowadays, echocardiography has been positioned as an essential tool in any ICU set to assess fluid status, ventricular ejection fraction, or any other myocardial complications. The high sympathetic tone in severely ill patients, in addition to high doses of adrenergic drugs often needed, may provoke a hypercontractile cardiac state. In the basis of our experience, we present a case of a patient with refractory septic shock and severe hemodynamic collapse, refractory to vasopressors with concomitant respiratory deterioration due to dynamic left ventricular outflow tract obstruction (LVOTO). Transesophageal echocardiography (TOE) was used to assess hemodynamic status and to guide treatment. A critical response to intravenous β-blockers was seen, with a dramatic decrease in vasopressor dosage and respiratory support.